(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The main aim of this paper is to propose a new and simple algorithm forÂ space-fractional telegraph equation, namely new fractional homotopy analysis transformÂ method (FHATM). The fractional homotopy analysis transform method is an innovativeÂ adjustment in Elzaki transform algorithm (ETA) and makes the calculation much sim-pler. The numerical solutions obtained by proposed method indicate that the approachÂ is easy to implement and computationally very attractive. Finally, several numerical ex-amples are given to illustrate the accuracy and stability of this method.